Accounting for the role of tax-benefit changes in shaping income inequality: A new method, with application to income inequality in Finland - Joonas Ollonqvist (Aboa Centre for Economics (ACE), 2021)
This paper introduces a new method of analysing how the changes in the tax-benefit-system have been reflected in income inequality. This method is a combination of microsimulation based decomposition (Bar gain and Callan, 2010) and a multivariate regression based decompo sition (Fields, 2003; Yun, 2006). It allows analysis of how the policy changes have affected the importance of different individual character istics in income inequality. With the variance of log of incomes, the decomposition can be made further to separate the changes directly related to policy decisions from the overall price- and residual effects. This method is applied to analyse the evolution of income inequality in Finland from 1993 to 2014.
Keywords: D31; H24; 330; income inequality; microsimulation; regression; tax-benefit system; decomposition